2015
DOI: 10.1016/j.adolescence.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The audience effect in adolescence depends on who's looking over your shoulder

Abstract: Adolescents have been shown to be particularly sensitive to peer influence. However, the data supporting these findings have been mostly limited to the impact of peers on risk-taking behaviours. Here, we investigated the influence of peers on performance of a high-level cognitive task (relational reasoning) during adolescence. We further assessed whether this effect on performance was dependent on the identity of the audience, either a friend (peer) or the experimenter (non-peer). We tested 24 younger adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 61 publications
(74 reference statements)
2
48
0
1
Order By: Relevance
“…For example, stronger observer effects might have been found if we had reminded adults that they were being watched and evaluated at the start of each trial. Also possible is that children generally have greater concerns with how they will be judged by others (Ruggeri et al, 2017;Wolf, Bazargani, Kilford, Dumontheil, Blakemore, 2015). Finally, our study is not unique in failing to find observer effects in adults.…”
Section: Discussionmentioning
confidence: 72%
“…For example, stronger observer effects might have been found if we had reminded adults that they were being watched and evaluated at the start of each trial. Also possible is that children generally have greater concerns with how they will be judged by others (Ruggeri et al, 2017;Wolf, Bazargani, Kilford, Dumontheil, Blakemore, 2015). Finally, our study is not unique in failing to find observer effects in adults.…”
Section: Discussionmentioning
confidence: 72%
“…In the 12-14-year-olds, mPFC activity was elevated when participants showed reciprocal behavior, whereas the other age groups showed similar levels of mPFC activity also when defecting others (Van den Bos et al, 2011). Thus, together with the prior behavioral studies these results indicate that younger adolescents may be more sensitive to social context (Wolf et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…Additionally, a recent study including adolescents found a hindering effect of an audience on adolescents' relational reasoning performance (Wolf et al, 2015). Younger adolescents (10-14 years), older adolescents (14-17 years) and adults (21-34 years) performed a relational reasoning task while alone, with an experimenter, or with a friend present.…”
Section: Social Influence On Cognitive Performancementioning
confidence: 99%